Inflated taxonomy in the West Mediterranean Temnothorax algiricus complex (Hymenoptera, Formicidae) revealed by quantitative morphology - Schifani, Enrico; Menchetti, Mattia; Csősz, Sándor; Vila, Roger (Zootaxa, 2025)
Temnothorax is one of the largest ant genera, with most taxa described from the Mediterranean. The western Mediterranean Temnothorax algiricus complex (Hymenoptera, Formicidae) is a well-defined lineage of dark-reddish arboreal species, whose taxonomy has never been comprehensively addressed. We conducted a comprehensive taxonomic revision using quantitative morphological analysis complemented by qualitative observations to clarify the systematic relationships within this group. Our analysis of 13 previously described taxa reveals only three valid species: T. algiricus (Forel, 1894), T. atlantis (Santschi, 1911), and T. trabutii (Forel, 1894). We establish several new synonymies: Leptothorax angustulus brunea Santschi, 1918, Leptothorax gazella Santschi, 1932, Leptothorax gazella monticola Santschi, 1932, Temnothorax mediterraneus Ward, Brady, Fisher, & Schultz, 2014, and Temnothorax atlantis veneris Galkowski & Cagniant, 2017 are considered junior subjective synonyms of T. algiricus. Leptothorax kiudiria Espadaler, 1997, Leptothorax angustulus silvanus (Forel, 1907), Temnothorax atlantis suturalis Galkowski & Cagniant, 2017, and Temnothorax continentalis Galkowski & Cagniant, 2017 are synonymized under T. atlantis. Leptothorax lindbergi Santschi, 1931 is considered a synonym of T. trabutii. Leptothorax convexus timida Santschi, 1912 is a junior synonym of Temnothorax convexus (Forel, 1894), and excluded from the complex. This revision resolves the oversplit nomenclature characteristic of North African myrmecology and establishes taxonomic consistency with European classifications. Our quantitative morphology-based framework provides the foundation for future integrative taxonomic studies investigating intraspecific variation and potential cryptic diversity within this ecologically important ant lineage.